Charcot-Marie-Tooth disease and dilated cardiomyopathy. A rare combination. - Rafael Pila Pérez; Víctor Adolfo Holguín Prieto; Leandro Segura Pujol (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The case of a 50 years old male patient is presented. Along 14 years of clinical evolution, four limbs musculoskeletal disorders with atrophy of the thenar and hypothenar prominences and muscles of both legs had been emphasized. The presence of sensory impairment in lower limbs with stocking distribution, atrophy, weakness, areflexia and equine gait were very peculiar in this case. From the cardiac point of view, the patient presented a fibrillation/flutter. Chest radiography showed a marked increase in the cardiac area and echocardiography revealed dilated cardiomyopathy. Histopathological examination confirmed the presence of Charcot-Marie-Tooth disease associated with dilated cardiomyopathy. While genetic studies are still lacking, diagnosis was based on clinical features, motor conduction velocity and histopathologic examination showing onion like demyelinating lesions. Charcot-Marie-Tooth is a rare disease.  Approximately 60% of patients who suffer from it carry chromosome 17 duplication, which is why it has been considered very appropriate to convey the experience of this case.